Reductive linear- and cyclo-trimerization of isocyanides using an Al–Al-bonded compound1. Issue 64 (19th July 2019) - Chen, Weixing; Zhao, Yanxia; Xu, Wenhua; Su, Ji-Hu; Shen, Lingyi; Liu, Li; Wu, Biao; Yang, Xiao-Juan
Abstract : Dialumane can promote cyclo-trimerization of isocyanides in the presence of Na, affording the product [Na][LAl{μ-η 1 :η 2 -( t BuNC)3 }Al(CN)L] with a unique aromatic tri( tert -butylimino)deltate dianion [C3 N3 ( t Bu)3 ] 2− . Abstract : Dialumane1 reacts with t BuNC to produce a reductive dimerization adduct [LAl( t BuNC–CN t Bu)AlL] (2 ). In the presence of Na, 1 can promote linear- and cyclo-trimerization of isocyanides, affording products [Na][LAl{( t BuNC)3 }AlL] (3 and4 ) and [Na][LAl{( t BuNC)3 }Al(CN)L] (5 ), the latter of which features a unique aromatic tri( tert -butylimino)deltate dianion [C3 N3 ( t Bu)3 ] 2− .